Prenatal assistance through the Programa Rede Mãe Paranaense in two border municipalities (Research, Society and Development, 2021)
This study sought to apprehend the experience of women who underwent prenatal care through the Programa Rede Mãe Paranaense Program in two municipalities on the international border strip. This is a qualitative research in the light of the phenomenological reference of Alfred Schütz, conducted with 18 women who were assisted in prenatal care by the program. For data collection, a phenomenological interview was used, and the analysis was followed according to the referential. Five categories were identified: knowledge about the program; access and reception in the health service; multiprofessional care and its peculiarities; health education; and women's perspectives regarding the program. The results point to a practice focused on the medical care model operated in a systematized way with little opening for dialogues, exchange of experiences and information, considering the particularities of the border area and the limitation of the study. Instigates reflections on prenatal care in the face of the program proposal that requires investments in training and actions of professionals.